KEMAMPUAN MANAJERIAL, DAN BUDAYA ORGANISASI TERHADAP KINERJA DOSEN DI LINGKUNGAN IAIN BENGKULU - Zulkarnain S (Universitas Islam Negeri Fatmawati Sukarno, 2017)
This means that good personality results in improved lecturer performance. Managerial ability has a positive direct effect on performance. This means that good managerial skills lead to improved lecturer performance. Organi- zational culture has a direct positive effect on performance. This means that a good organizational culture, resulting in improved lecturer performance. Personality has a direct positive effect on organizational culture. This means that a good personality leads to an increase in organizational culture. Managerial ability has a direct positive effect on organi- zational culture. This means that good managerial skills, resulting in increased organizational culture